2010
DOI: 10.1029/2010gl045233
|View full text |Cite
|
Sign up to set email alerts
|

Present‐Day Volcanism on Venus: Evidence from Microwave Radiometry

Abstract: We present new evidence for volcanic eruptions and lava flow emplacement on Venus within the last several decades. An integrated study of a radar‐dark lava flow unit in Bereghinia Planitia on Venus (∼28°E, ∼39°N) based on Magellan data obtained in 1993 reveals a significant apparent microwave thermal emission excess, consistent with increased subsurface temperature due to very recent lava flow emplacement. The flow unit occupies the stratigraphically youngest position in the area and in part is more than 15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…However, the indirect evidence (of changes in the sulphur dioxide abundance in the atmosphere) has alternative explanations. The claimed direct evidence of microwave (Bondarenko et al 2010) andnear-infrared (e.g., Shalygin et al 2012) emission is subject in both cases to high false-positive susceptibility due to the background subtraction or modeling required to isolate a volcanic signature, and the claims are not widely considered adequate evidence to assert discovery.…”
Section: Lightning and Volcanosmentioning
confidence: 99%
“…However, the indirect evidence (of changes in the sulphur dioxide abundance in the atmosphere) has alternative explanations. The claimed direct evidence of microwave (Bondarenko et al 2010) andnear-infrared (e.g., Shalygin et al 2012) emission is subject in both cases to high false-positive susceptibility due to the background subtraction or modeling required to isolate a volcanic signature, and the claims are not widely considered adequate evidence to assert discovery.…”
Section: Lightning and Volcanosmentioning
confidence: 99%
“…The principal determinants of microwave transparency are liquid water content, and the amount of certain iron minerals: water ice well below the freezing point (so that no films of water are present) and dry silica sand are notably transparent materials. Bondarenko et al (2010) have suggested that microwave radiometry should be able to detect lava flows on Venus that are months-years old, by probing to depths where the lava is still hundreds of kelvin above ambient. Essentially the detectability of a buried lava flow relates to the ratio of the electrical skin depth (to which the instrument is sensitive) to the thermal skin depth (to which the lava has cooled).…”
Section: Introductionmentioning
confidence: 99%
“…On Venus and Titan, optically-thick atmospheres and other factors challenge this approach, and so microwave sensing has been proposed as a means to detect 'hot spots' (e.g. Bondarenko et al, 2010;Lopes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the radiometer will look at the nadir radio emissions and averaged over the same interval as the altimeter, the two datasets can be directly correlated to determine C-band atmospheric transmissivity. Crosscorrelating the data in this way improves the confidence in the detection of real emission sources, such as the still-warm lava flows recently inferred (Bondarenko et al, 2010) from Magellan data.…”
Section: Radiometer and Altimeter Modementioning
confidence: 99%